The strategy for developing virgin coconut oil (vco) products at IKM Al Huda 45 in Kontumolepe Village, Tongkuno District, Muna Regency using SWOT analysis - Bintang Ibrahim; Sukmawati Abdullah; La Rianda (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2022)
Penelitian ini bertujuan untuk mengetahui strategi pengembangan produk virgin coconut oil pada IKM Al Huda 45 di Kelurahan Kontumolepe Kecamatan Tongkuno kabupaten Muna. Metode penelitian yang digunakan adalah Analisis SWOT, Matriks Evaluasi Faktor Eksternal (Eksternal Factor Evaluation- EFE Matrix), Matriks This study aims to determine the strategy for developing virgin coconut oil products at IKM Al Huda 45 in Kontumolepe Village, Tongkuno District, Muna Regency. The research method used is the SWOT analysis, External Factor Evaluation Matrix (EFE Matrix), and Internal Factor Evaluation Matrix (IFE Matrix). Data was collected using a questionnaire, interview, documentation and observation methods. The results showed that the analysis of the development strategy showed the results on the Internal Factor Evaluation (IFE) matrix with a total weight score owned by the Al Huda 45 business of 2.75, which indicated that the position of the Al Huda 45 IKM had an internal position that was above the average. Meanwhile, the total score for External Factor Evaluation (EFE) is 3.00, which indicates that the business position is relatively high in IKM Al Huda 45 in dealing with external dynamics. Strength development strategies take advantage of existing opportunities by (1) maintaining the quality of virgin coconut oil products made from coconut to meet product demand, (2) increasing the amount of production and quality of virgin coconut oil to meet market demand, (3) increasing promotions and (4) utilizing government assistance in reducing production costs. From the analysis of the Al Huda 45 IKM development strategy, it is feasible to be developed.